Light-emitting properties of BN synthesized by different techniques - Rudko, G. Yu; Sartinska, L. L.; Isaieva, O. F.; Gule, E. G.; Eren, T.; Altay, E. (NATL ACAD SCIENCES UKRAINE, INST SEMICONDUCTOR PHYSICS, 2020)
Light-emitting properties of boron nitride powders of different morphology grown using various techniques have been studied. All samples were hexagonal BN (h-BN), while the content of impurity phases varied considerably. The wide photoluminescence band in the visible range has been observed. h-BN synthesized using carbothermal reduction method exhibited the highest efficiency of the photoluminescence emission. The intensity of BN emission has been interpreted in terms of interplay between the emission of intrinsic defects stabilized by carbon, carbon-related recombination centers and the centers of non-radiative recombination caused by the presence of sassolite phases in the samples.
Keywords: boron nitride; nanostructures; XRD; SEM; photoluminescence; HEXAGONAL BORON-NITRIDE; LUMINESCENCE PROPERTIES; BCNO; NANOTUBES; SPECTROSCOPY; CARBON; Physics